Pengaruh Suasana Hati Terhadap Kinerja Karyawan : Studi Kasus Karyawan Mbizmarket di PT. Brilliant Ecommerce Berjaya - Usran Masahere; Fadli Ilyas (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
Performance is a working activity conducted by the employees in a timeframe that had already designed for their evaluation. One of the factors that utilized as a background is the mood. The objective of this research is to find out the influence of mood toward Mbizmarket staff’s performance in PT Brilliant Ecommerce Berjaya. This research utilizes qualitative descriptive approach. The subjects of this research are five staffs in PT Brilliant Ecommerce Berjaya. The outcome of this research shows that both internal and external factors within inner self of employees also form their mood in their working days. Mood has a characteristic component which is attached on every individual. The majority of Mbizmarket’s staffs had already built tendency to experience particular mood by the rolling of time suitable to the internal and external factors. The staffs have various moods based on time and day. Therefore, most of them follow the same frequent patterns from social creature’s natural behavior according to their interaction patterns.